Sumber-Sumber Pertumbuhan Ekonomi Jawa Timur Periode 2000-2010: Analisis Dekomposisi Struktural - Ali Akbar Hakim; Bambang Eko Afiatno (Trunojoyo University of Madura, 2022)
The purpose of this study was to determine the sources of economic growth in East Java using structural decomposition analysis. The study period is divided into two periods, namely the initial period (2000-2006) and the final period (2006-2010). The results show in the early period indicate that changes in final demand are the main determinants of economic growth in almost all sectors of the East Java economy, while changes in production structure (technology effects) tend to have negative effects on growth in almost all sectors other than services. In the final period, improvements to the production structure in almost every sector were able to make a positive contribution to output. Among the final demand categories, the largest output growth came from exports (between provinces) in the initial period, while in the final period the main source of growth shifted to household consumption. These findings indicate that East Java has the potential for large economic growth through inter-province exports with the support of improved production structures, particularly in the manufacturing sector.